Depictions of children and the adult's journey in the arts - Georgieva, Margarita (Cambridge Scholars Publishing, 2017)
Why do adults write about the child and why do they choose to depict children? This book looks at various examples from literature, art and film to analyze aspects of adults' outlook on the child, and what it tells us about the adult. It pays special attention to the eye motif, as well as looking, watching and representing children. It outlines what might become an interesting topic of analysis for other studies, namely, the idea that the adult's journey to self-actualization passes through writing for and about children. Rather than drawing major conclusions, the book opens venues for further.